Infográfico animado para o idoso com doenças crônicas e sua relação com a saúde bucal - Xavier Júnior, José Alves (2019)
Introduction: The continuation of life is a wish of any society, mainly in view of the phenomenon of aging, by reason of the reduction of the capacity of the elderly due to physical changes, biochemical and functional. This amendment makes the elderly more prone to develop chronic diseases, behold, one of the risk factors is the age itself, although this does not mean an obstacle to healthy aging. Chronic diseases are affections of health that extend through time, alternating between improvement and worsening of the symptoms, being a health problem worldwide, evidenced in low- and middle-income countries, and the main cause of morbidity and mortality in Brazil. There prove effects of chronic diseases in oral health, which is why the oral health gains prominence in the process of systemic care. In this perspective, the relationship between chronic diseases and oral health of the elderly makes it necessary to build actions directed to the health of this population. Objectives: 1) To demonstrate the scientific publications on chronic diseases and the oral health of the elderly person. 2) To check the impact of chronic diseases in oral health of the elderly person. 3) To propose an animated infographic for elderly people with chronic diseases and the impact on oral health. Methodological Path: This is an exploratory study with a quantitative approach, in conjunction with a methodological research, with submission in its final phase, a technological instrument with data on oral health of the elderly and their relation with the chronic diseases, in the form of an infographic excited. Results and Discussion: There were produced: A) An integrative review article “Chronic diseases and oral health of the elderly: an integrative review”, with analysis of nine articles in the final sample, in which the context has been clarified the relationship between chronic diseases and the oral health of the elderly. Moreover, as the existence of unsatisfactory conditions in the oral cavity of this population. B) A second article because of a search in a Center for Integrative Practices of the municipality of João Pessoa/Paraiba, on the impact of chronic diseases in oral health of the elderly. The results pointed to the understanding that the oral health care is one of the pillars for the maintenance of systemic health. (C) An infographic lively drawn from the results obtained, directed to the elderly with chronic diseases, with the purpose to demonstrate the correlation of chronic diseases in the elderly and the impact on oral health. Conclusion: The integrative review showed the correlation between chronic diseases and the oral health of the elderly. According to the survey, the elderly with chronic diseases claim to have received guidance on oral health; however, high percentage did not attend to any dental consultations in the last year. It expects that, with the use of the infographic lively correlating the chronic diseases with oral health, the elderly can be motivated to care with oral health and be stimulated to appropriate monitoring with the odontogeriatician.